Draft And Implementation Time Value of Money in Financial Decision Making - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; Abdul Rahma; Rachmat Al Fadjri (CV. RADJA PUBLIKA, 2025)
Time Value of Money (TVM) is a fundamental concept in financial science which explains that the value of money today is more valuable than the value of the same money in the future. front. Difference mark the influenced by factor time, level ethnic group flower, risk, and inflation. This study aims to examine the concept and application of Time Value of Money in financial decision making through a literature review approach. The method used in this study is a literature study by reviewing various scientific sources in the form of financial textbooks and national and international journals that are relevant to Time Value topic of Money . The data that obtained analyzed in descriptive and This study aims to identify the main concepts, influencing factors, and implications of the application of Time Value of Money in investment, financing, and financial planning decisions. The results of the study indicate that understanding the concept of Time Value of Money plays a significant role in improving the quality of financial decision-making. The application of the time value of money allows individuals and organizations to evaluate decision alternatives rationally, objectively, and with a long-term orientation. Furthermore, the literature also confirms that low financial literacy can be an obstacle to the optimal application of this concept. The conclusion of this study confirms that Time Value of Money is not only theoretical but also has significant practical implications. in support taking decision finance Which effective And Therefore, improving understanding of the concept of Time Value of Money is important for individuals, practitioners, and educational institutions.